2005
DOI: 10.1123/jpah.2.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity in Persons with Arthritis: Review and Recommendations

Abstract: Background: Physical activity (PA) is important for arthritis self-management. A better understanding of the PA correlates in persons with arthritis will help inform interventions. Methods: Computer searches were conducted on PubMed, PsychInfo, Current Contents, and Cinahl databases. Reference lists of extracted articles were also searched. Thirty-six studies published between 1976 and February 2004 met inclusion criteria. Results: PA correlates are presented for sociodemographic, psychological, health-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 49 publications
(127 reference statements)
5
43
2
3
Order By: Relevance
“…However, inconsistencies exist in the relationship between pain and actual amounts of physical activity (Wilcox, Der Ananian, Sharpe, Robbins, & Brady, 2005). Some individuals manage to engage in more activity than others despite this apparent obstacle Gyurcsik et al, 2009;Hendry, Williams, Markland, Wilkinson, & Maddison, 2006;Wilcox et al, 2006).…”
Section: Arthritis Pain and Physical Activitymentioning
confidence: 98%
“…However, inconsistencies exist in the relationship between pain and actual amounts of physical activity (Wilcox, Der Ananian, Sharpe, Robbins, & Brady, 2005). Some individuals manage to engage in more activity than others despite this apparent obstacle Gyurcsik et al, 2009;Hendry, Williams, Markland, Wilkinson, & Maddison, 2006;Wilcox et al, 2006).…”
Section: Arthritis Pain and Physical Activitymentioning
confidence: 98%
“…[64][65][66] Although not extensive, there is evidence from research reviews and studies that both environmental contextual and personal contextual factors (i.e., ICF factors; see Figure 1) are associated with physical activity adherence in people with arthritis. [67][68][69][70][71] Environmental factors for which there is evidence of a positive relationship with adherence include increased social support (including physical activity advice from health care providers) and decreased work/family responsibilities. Personal contextual factors for which there is evidence of a positive association with adherence include lower pain, higher perceived well-being, no evidence of depression, fewer barriers, and increased self-regulatory efficacy (which revolves around confidence beliefs important for performing regular activity, such as scheduling/planning, coping with barriers, and goal setting).…”
Section: The Relationship Of Balance and Walking Limitations To Incrementioning
confidence: 99%
“…The central role that attitudes and beliefs play in determining health-related behavior, including exercise, is highlighted in many social cognitive models (summarized by Horne and Weinman [13]), and existing evidence supports the link between the attitudes and beliefs of older adults with knee pain and their exercise and physical activity behavior (14,15). Some qualitative studies have already suggested that individuals may hold unhelpful attitudes and beliefs about their knee problems and about the role of exercise in managing their pain, which could be a barrier to exercise and physical activity behavior (16,17).…”
Section: Introductionmentioning
confidence: 99%